How to draw vampires - Butkus, Mike (Fantasy underground., 2010)
Discover the folklore and history of vampires, and learn how they were transformed from a ghoulish demon into a romantic charmer. Discover how to capture the vampire in pencil, acrylic and oil, and create your own undead beast.